2021
DOI: 10.1016/j.eclinm.2020.100692
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and cause-specific mortality in Cuba: prospective study of 120 623 adults

Abstract: Background The associations of cause-specific mortality with alcohol consumption have been studied mainly in higher-income countries. We relate alcohol consumption to mortality in Cuba. Methods In 1996-2002, 146 556 adults were recruited into a prospective study from the general population in five areas of Cuba. Participants were interviewed, measured and followed up by electronic linkage to national death registries until January 1, 2017. After excluding all with missi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 22 publications
0
17
0
1
Order By: Relevance
“…There were 724 estimates of the risk relationship between level of alcohol consumption and all-cause mortality from 107 unique studies, including 4 838 825 participants and 425 564 deaths available for the analysis. Table 1 describes the sample characteristics of the metadata.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were 724 estimates of the risk relationship between level of alcohol consumption and all-cause mortality from 107 unique studies, including 4 838 825 participants and 425 564 deaths available for the analysis. Table 1 describes the sample characteristics of the metadata.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 describes the sample characteristics of the metadata. Of 39 studiesreporting RR estimates for men and women separately, 33 were for males only, 8 for females only, and 30 for both sexes. Twenty-one studies (220 risk estimates) were free from abstainer bias (ie, had a reference group of strictly defined lifetime abstainers).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even more recent observational studies have focused on specific niches of the relationship between alcohol consumption and CVD, testing the hypothesis that the relationship between alcohol and CVD does not fit into a one-size-fits-all approach and that the conflicting results found in previous studies might be due to differences within subpopulations. For example, investigators have observed apparent differences in the alcohol-CVD relationship between African-Americans, Asian-Americans and other race/ethnicity groups found [ 28 32 ] (perhaps related to well-known genetic differences in alcohol metabolism [ 33 , 34 ]). Other recent papers have addressed drinking patterns, suggesting that regular drinking and drinking with meals may be associated with a lower risk of mortality [ 35 37 ] and beverage types, arguing for unique anti-oxidative and anti-inflammatory effects of red wine consumption [ 38 ].…”
Section: Evidence From Observational Researchmentioning
confidence: 99%
“…A prospective study conducted in Cuba revealed that weekly alcohol consumption was positively associated with premature mortality from all causes, and the risk of death from any cause increased by 10% for each bottle of rum (the main drink consumed in the country) added weekly. The main causes of excessive mortality were cancers, vascular diseases and external causes [ 4 ].…”
Section: Introductionmentioning
confidence: 99%